2015
DOI: 10.1089/neu.2014.3669
|View full text |Cite
|
Sign up to set email alerts
|

Neurotransmitter Systems in a Mild Blast Traumatic Brain Injury Model: Catecholamines and Serotonin

Abstract: Exposure to improvised explosive devices can result in a unique form of traumatic brain injury-blast-induced traumatic brain injury (bTBI). At the mild end of the spectrum (mild bTBI [mbTBI]), there are cognitive and mood disturbances. Similar symptoms have been observed in post-traumatic stress disorder caused by exposure to extreme psychological stress without physical injury. A role of the monoaminergic system in mood regulation and stress is well established but its involvement in mbTBI is not well underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 85 publications
4
38
1
Order By: Relevance
“…Such experiments could be combined with biomarker sampling, behavior analysis such as the Forced Swim Test and functional imaging. A recent study has revealed significant changes in catecholamines and serotonin in rodents exposed to a mild TBI (Kawa et al, 2014).…”
Section: Preclinicalmentioning
confidence: 99%
See 1 more Smart Citation
“…Such experiments could be combined with biomarker sampling, behavior analysis such as the Forced Swim Test and functional imaging. A recent study has revealed significant changes in catecholamines and serotonin in rodents exposed to a mild TBI (Kawa et al, 2014).…”
Section: Preclinicalmentioning
confidence: 99%
“…Such experiments could be combined with biomarker sampling, behavior analysis such as the Forced Swim Test and functional imaging. A recent study has revealed significant changes in catecholamines and serotonin in rodents exposed to a mild TBI (Kawa et al, 2014).One way to accomplish a better translation between animal experiments and the clinic would be to employ the same methodology for analysis. Imaging, e.g.…”
mentioning
confidence: 99%
“…Traumatic brain injury (TBI) causes serious adverse outcomes including death and disability in both industrialized countries (Coronado et al 2011) and developing countries (Kawa et al 2014;Sarkar et al 2014). Two phases of TBI have been identified: primary injury and an ensuing secondary reaction.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported earlier that miRNAs may play a role in PTSD pathophysiology [47]. A recent study by Kawa et al [75] shows a correlation of increase in tryptophan hydroxylase 2, a rate-limiting enzyme for serotonin synthesis, with anxiety-like behaviour in the brain after mTBI. Similarly, this study has reported depression and emotional distress in the mice using the same mTBI model as previously used [13].…”
Section: Discussionmentioning
confidence: 63%